2012
DOI: 10.3102/0013189x12459678
|View full text |Cite
|
Sign up to set email alerts
|

Are Minority Children Disproportionately Represented in Early Intervention and Early Childhood Special Education?

Abstract: We investigated whether and to what extent children who are racial/ethnic minorities are disproportionately represented in early intervention and/or early childhood special education (EC/ECSE). We did so by analyzing a large sample of 48-month-olds (N=7,950) participating in the Early Childhood Longitudinal Study-Birth Cohort (ECLS-B), a nationally representative dataset of children born in the U.S. in 2001. Multivariate logistic regression analyses indicate that boys (OR=1.66), children born at very low birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 74 publications
(122 reference statements)
6
95
0
2
Order By: Relevance
“…Yet substantial underidentification for the general sample was also observed, with only 29% of children meeting diagnostic criteria for specific language impairment subsequently reported by their parents to be receiving services. Other studies have also found that children who are minorities are less likely to be identified as delayed or disabled (Hibel, Farkas, & Morgan, 2010;McManus, McCormick, Acevedo-Garcia, Ganz, & HauserCram, 2009;Morgan et al, 2015) including during the early childhood years (Morgan et al, 2012;Samson & Lesaux, 2009). Delgado and Scott's (2006) analysis of preschool referral rates in Florida indicated that children who are racial/ethnic minorities were less likely to be referred for services.…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 98%
See 4 more Smart Citations
“…Yet substantial underidentification for the general sample was also observed, with only 29% of children meeting diagnostic criteria for specific language impairment subsequently reported by their parents to be receiving services. Other studies have also found that children who are minorities are less likely to be identified as delayed or disabled (Hibel, Farkas, & Morgan, 2010;McManus, McCormick, Acevedo-Garcia, Ganz, & HauserCram, 2009;Morgan et al, 2015) including during the early childhood years (Morgan et al, 2012;Samson & Lesaux, 2009). Delgado and Scott's (2006) analysis of preschool referral rates in Florida indicated that children who are racial/ethnic minorities were less likely to be referred for services.…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 98%
“…Recent analyses by McManus et al (2013) of a very low birth weight cohort similarly did not include vocabulary delays as a predictor. Morgan et al (2012) reported that 48-month-old children with greater receptive vocabulary knowledge were less likely to be identified as developmentally delayed or disabled, including being diagnosed for communication problems. Yet they did not examine whether this relation with vocabulary knowledge extended specifically to speech/language service use or to the earlier onset of expressive vocabulary delays.…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 99%
See 3 more Smart Citations